For the function f (x) = x + 1/x , x ∈ [1, 3], the value of c for mean value theorem is
(A)1
(B) √3
(C) 2
(D) None of these
This question is similar to Example 43 - Chapter 5 Class 12 - Continuity and Differentiability
NCERT Exemplar - MCQs
Question 2 Important
Question 3
Question 4 You are here
Question 5
Question 6 Important
Question 7 Important
Question 8
Question 9 Important
Question 10
Question 11
Question 12 Important
Question 13
Question 14 Important
Question 15
Question 16 Important
Question 17
Question 18 Important
Question 19
Question 20
Question 21 Important
Question 22
Question 1 Important
Question 2
Question 3
Question 4 Important You are here
NCERT Exemplar - MCQs
Last updated at April 16, 2024 by Teachoo
This question is similar to Example 43 - Chapter 5 Class 12 - Continuity and Differentiability
Question 4 For the function f (x) = x + 1/𝑥 , x ∈ [1, 3], the value of c for mean value theorem is 1 (B) √3 (C) 2 (D) None of these 𝑓(𝑥)="x + " 1/𝑥 in interval [1, 3] Checking conditions for Mean value Theorem Conditions of Mean value theorem 𝑓(𝑥) is continuous at {𝑎, 𝑏} 𝑓(𝑥) is differentiable at (𝑎 , 𝑏) If both conditions satisfied, then there exist some c in (𝑎 , 𝑏) such that 𝑓′(𝑐) = (𝑓(𝑏) − 𝑓(𝑎))/(𝑏 − 𝑎) Condition 1 We need to check if 𝑓(𝑥)="x + " 1/𝑥 is continuous in the interval [1, 3] Let 𝒈(𝒙)=𝒙 and 𝐡(𝒙)=𝟏/𝒙 We know that, 𝒈(𝒙)=𝑥 is continuous as it is a polynomial function And, 𝐡(𝒙)=1/𝑥 is continuous for all 𝑥 except for 𝒙=𝟎 ∴ h(𝑥)=1/𝑥 is continuous in the interval [1, 3] Hence, 𝒇(𝒙)=𝒈(𝒙)+𝒉(𝒙) is also continuous in the interval [1, 3] Condition 2 We need to check if 𝑓(𝑥)="x + " 1/𝑥 is differentiable at ("1, 3") A function is said to be differentiable if the derivative of the function exists. Differentiating 𝑓(𝑥) wrt 𝑥 𝒇^′ (𝒙)=𝟏−𝟏/𝒙^𝟐 Since, derivative of the given function exists Hence, 𝒇(𝒙) is differentiable at ("1, 3") Since both conditions are satisfied From Mean Value Theorem, There exists a c ∈ (1, 3) such that, 𝑓^′ (𝑐) = (𝑓(3) − 𝑓(1))/(3 −1) 𝟏−𝟏/𝒄^𝟐 = ((𝟑 + 𝟏/𝟑) − (𝟏 + 𝟏/𝟏))/𝟐 1−1/𝑐^2 = ((9 + 1)/3 − 2)/2 1−1/𝑐^2 = (10/3 − 2)/2 1−1/𝑐^2 = ((10 − 6)/3)/2 1−1/𝑐^2 = 4/(3 × 2 ) 𝟏−𝟏/𝒄^𝟐 = 2/3 𝟏−𝟐/𝟑= 𝟏/𝒄^𝟐 (𝟑 − 𝟐)/𝟑= 𝟏/𝒄^𝟐 𝟏/𝟑= 𝟏/𝒄^𝟐 𝑐^2=3 𝑐=±√3 𝒄=±𝟏.𝟕𝟑 Either, c = −1.73 But, −1.73 ∉(𝟏, 𝟑) Or, c = 1.73 And, 1.73 ∈ (𝟏, 𝟑) Therefore, 𝒄=√𝟑 So, the correct answer is (B)